Grammatical Representations of the Verb Phrase in Mandarin Chinese: Evidence from Syntactic Priming in Five-Year-Olds - Dong-Bo Hsu (Brain Sciences)
Background/Objectives: Debates regarding how to represent verb phrases (VPs) consisting of the verb plus the complement and the aspectual marker -le in Mandarin Chinese remain an issue. Methods: Syntactic priming under a memory disguise paradigm was employed to investigate the issue using the SVO-ba alternation, where the SVO structure consists of a subject verb object, and the ba structure of a subject ba object verb, in five-year-olds (n = 216), an age with fully fledged grammatical knowledge but little interference from literacy. Results: The results indicate that both the complement and the marker -le should be represented in terms of phrasal rather than morphological structures. When -le is inflected to the verb alone, realization, which makes an event a fact, rather than completion, which makes an event finished, is accomplished. The event must be telicized to a state through a resultative complement to induce reliable production of the ba construction. The postverbal elements represent their own phrasal structure and challenge the verb-centered lexico-syntactic account because there are no additional representations left within a verb. Conclusions: More elicitations of the SVO than the ba invite future neurolinguistic explorations to disentangle the impacts of the frequency and thematic arrangement of agent and patient on grammatical representations cross-linguistically.